NAC Gene Family in Lagerstroemia indica: Genome-Wide Identification, Characterization, Expression Analysis, and Key Regulators Involved in Anthocyanin Biosynthesis - Zilong Gao; Zhuomei Chen; Jinfeng Wang; Weixin Liu (Current Issues in Molecular Biology)
NAC (NAM, ATAF1/2, CUC1/2) is a plant-specific transcription factor (TF) family that plays important roles in various physiological and biochemical processes of plants. However, the NAC gene family in Lagerstroemia indica and its role in anthocyanin metabolism are still unexplored. In our study, a total of 167 NACs were identified in the L. indica genome via genome-wide analysis and bioinformatics techniques. Amino acid sequence analysis showed that all 167 NAC proteins contained a conserved NAM domain. This domain primarily comprised random coils, extended strands, and alpha helices. Most NACs were found on the nucleus and dispersed over 23 of the 24 plant chromosomes. Based on phylogenetic analysis, the NACs can be categorized into ten subgroups. Furthermore, the promoter homeotropic elements predicted the cis-acting elements in the promoters of these genes related to hormones, development, environmental stress response, and other related responses, demonstrating the diverse regulatory mechanisms underlying gene functions. In addition, a co-expression network was established through RNA sequencing. This network helped identify seven key LiNACs, genes related to anthocyanin expression (CHS) and transcription factors (MYB and bHLH). To identify potential anthocyanin regulatory factors present in L. indica petals, protein interaction prediction was performed, which revealed that LiNACs might participate in anthocyanin regulation by interacting with other proteins, such as MYB, ABF, ABI, bZIP, MYC, etc. Our results provided novel insights and could help in the functional identification of LiNACs in L. indica and the regulation of anthocyanin synthesis.